Gender Bias in Human Systemic Lupus Erythematosus: A Problem of Steroid Receptor Action? - Rider, Virginia; Abdou, Nabih I.; Kimler, Bruce F.; Lu, Nanyan; Brown, Susan; Fridley, Brooke L. (Frontiers in Immunology, 2018)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease resulting from abnormal interactions between T and B cells. The acquisition of SLE is linked to genetic susceptibility, and diverse environmental agents can trigger disease onset in genetically susceptible individuals. However, the strongest risk factor for developing SLE is being female (9:1 female to male ratio). The female sex steroid, estradiol, working through its receptors, contributes to the gender bias in SLE although the mechanisms remain enigmatic. In a small clinical trial, monthly administration of the estrogen receptor (ERα) antagonist, ICI182,780 (fulvestrant), significantly reduced disease indicators in SLE patients. In order to identify changes that could account for improved disease status, the present study utilized fulvestrant (Faslodex) to block ERα action in cultured SLE T cells that were purified from blood samples collected from SLE patients (n =18, median age 42 years) and healthy control females (n = 25, median age 46 years). The effects of ERα antagonism on estradiol-dependent gene expression and canonical signaling pathways were analyzed. Pathways that were significantly altered by addition of Faslodex included T helper (Th) cell differentiation, steroid receptor signaling [glucocorticoid receptor (GR), ESR1 (ERα)], ubiquitination and sumoylation pathways. ERα protein expression was significantly lower (p <0.018) in freshly isolated, resting SLE T cells suggesting ERα turnover is inherently faster in SLE T cells. In contrast, ERα/ERβ mRNA and ERβ protein levels were not significantly different between SLE and normal control T cell samples. Plasma estradiol levels did not differ (p > 0.05) between SLE patients and controls. A previously undetected interaction between GR and ERα signaling pathways suggests posttranslational modification of steroid receptors in SLE T cells may alter ERα/GR actions and contribute to the strong gender bias of this autoimmune disorder.